(x-2)(x-5)=-2

Simple and best practice solution for (x-2)(x-5)=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-2)(x-5)=-2 equation:


Simplifying
(x + -2)(x + -5) = -2

Reorder the terms:
(-2 + x)(x + -5) = -2

Reorder the terms:
(-2 + x)(-5 + x) = -2

Multiply (-2 + x) * (-5 + x)
(-2(-5 + x) + x(-5 + x)) = -2
((-5 * -2 + x * -2) + x(-5 + x)) = -2
((10 + -2x) + x(-5 + x)) = -2
(10 + -2x + (-5 * x + x * x)) = -2
(10 + -2x + (-5x + x2)) = -2

Combine like terms: -2x + -5x = -7x
(10 + -7x + x2) = -2

Solving
10 + -7x + x2 = -2

Solving for variable 'x'.

Reorder the terms:
10 + 2 + -7x + x2 = -2 + 2

Combine like terms: 10 + 2 = 12
12 + -7x + x2 = -2 + 2

Combine like terms: -2 + 2 = 0
12 + -7x + x2 = 0

Factor a trinomial.
(3 + -1x)(4 + -1x) = 0

Subproblem 1

Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3

Subproblem 2

Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4

Solution

x = {3, 4}

See similar equations:

| -1.3=-1.1+0.9 | | 3(x+4)=3x+14-2 | | 3m+6-13m=-2-14m | | 392=7x-7 | | -5(-5x-6)=22-x | | X^2-45x=0 | | -1=5x+12 | | -8+1=y+4-16 | | x+-37=19 | | 56-16+4c=48 | | (3x+10)=(4x-40) | | 3b-5-5b-3= | | 2x+3=x+5+x | | 15=5x+60 | | X*15=12 | | 46=n-13 | | -12y-3=-11y+8 | | (x+7)(x-3)=11 | | (10x-18)=(8x+14) | | 26+0.15p=c | | 6(W-3)=6W-18 | | 16-5*3= | | 8x-15=4x-(-12) | | 6=3(m+5)+3(m+3) | | 64x^3-81x=0 | | 10=x-15 | | 0.2p=9 | | 10=5(x-2)+5x | | s=0.1666666667w | | (68-x)=3x | | 100x^3-121x=0 | | 94=7x+17 |

Equations solver categories